The RECK gene and invasive cancer development - Alexius Lindgren, Michelle (2014)
The RECK gene is a relatively new discovered gene with important implications for cancer research. The research has been primarily concentrated on the human gene with the ultimate aim to identify the invasive characteristics. Up regulated RECK is linked to significantly prolonged survival rates in patients with severe forms of malignancies.